2009
DOI: 10.1021/es9022738
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Management on Cadmium and Arsenic Accumulation and Dimethylarsinic Acid Concentrations in Japanese Rice

Abstract: Rice consumption is a major source of cadmium and arsenic for the population of Asia. We investigated the effects of water management in rice paddy on levels of cadmium and arsenic in Japanese rice grains. Flooding increased arsenic concentrations in rice grains, whereas aerobic treatment increased the concentration of cadmium. Flooding for 3 weeks before and after heading was most effective in reducing grain cadmium concentrations, but this treatment increased the arsenic concentration considerably, whereas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
254
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 485 publications
(299 citation statements)
references
References 14 publications
13
254
1
1
Order By: Relevance
“…The aerobic treatment resulted in higher Cd concentrations in the soil solution but the flooding treatment gave lower Cd concentrations during the growing season. Arao et al (2009) also reported that Cd concentrations in the soil solution were below the detection limit during the time of flooding but increased during aerobic conditions. These results can be explained by the combining of Cd with S to form CdS at low redox potential under flooding conditions (Bingham et al, 1976).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The aerobic treatment resulted in higher Cd concentrations in the soil solution but the flooding treatment gave lower Cd concentrations during the growing season. Arao et al (2009) also reported that Cd concentrations in the soil solution were below the detection limit during the time of flooding but increased during aerobic conditions. These results can be explained by the combining of Cd with S to form CdS at low redox potential under flooding conditions (Bingham et al, 1976).…”
Section: Discussionmentioning
confidence: 97%
“…Selection and breeding of rice cultivars with low As and Cd accumulation have been practiced to reduce As and Cd in the rice grains (Zhang and Duan, 2008;Li et al, 2012;Ye et al, 2012). Water management is another promising method that affects Cd and As bioavailability in soils and their subsequent uptake by rice (Arao et al, 2009;Rahaman et al, 2011;Hu et al, 2013b). When a paddy field is flooded and the soil has a low redox potential, any Cd present in the soil combines with sulfur (S) to form CdS which has low solubility in water (Bingham et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This inhibitory effect of Si is supported by many laboratory experiments (Bogdan and Schenk 2008;Li et al 2009;Fleck et al 2013;Tripathi et al 2013). Areao et al (2009) reported that the soil Eh value decreased rapidly during the flooded period. In this case, arsenite as the predominant form of As species in paddy soils (reducing environments) is actually present in solution predominantly as an undissociated molecule at pH <8.…”
Section: Discussion Effect Of Si On As Concentration In Rice Grainmentioning
confidence: 66%